Formulasi, Evaluasi, dan Uji Aktivitas in Vivo Kapsul Ekstrak Daun Pepaya California (Carica papaya L.) pada Model Zebrafish - Adelia Putri Callysta; Feris Dzaky Ridwan Nafis; Anis Puji Rahayu (Universitas Muhamadiyah Manado, 2026)
California papaya leaves (Carica papaya L.) are known to contain various active compounds that have the potential to stimulate appetite and boost metabolism, making them a promising candidate for development as a pharmaceutical formulation. This study aims to design a capsule formulation of California papaya leaf extract with appropriate excipients and to evaluate its ability to increase body weight through preclinical testing using a zebrafish (Danio rerio). The extract was obtained via maceration with 96% ethanol and formulated into capsules using the wet granulation method in four variations (F0–F3). Physical evaluations included organoleptic properties, flowability, angle of repose, loss on drying, disintegration time, weight uniformity, and stability testing using the cycling test method. The results indicated that all formulas met the physical requirements, with disintegration times of 3–4 minutes and loss on drying <15%. Formula F2 exhibited the most optimal physical characteristics; however, stability testing revealed a decline in physical properties after extreme temperature treatment. Efficacy tests showed a significant increase in zebrafish weight (p < 0.05), with F3 yielding the best results. A high survival rate (≥80%) suggests the formulation is relatively safe. In conclusion, California papaya leaf extract capsules demonstrate significant potential as an agent to promote weight gain.